“I Will Make the Treaty”: Breaking the Executive Branch’s Monopoly over Foreign Policy through Constructive Use of Dissent - Elad Gross (Washington University Journal of Law & Policy, 2014)
Foreign relations and treaty making are essential functions of any legitimate government. The President has the authority to make international agreements on behalf of the United States, and the Senate or Congress as a whole must approve any treaties. But those with the most knowledge of the subject—the officials sitting at the negotiating table or working in the foreign embassy—do not have the ultimate say in whether a foreign relations policy or treaty is presented to Congress for consideration; that power lies exclusively with the President. In response to increasingly vocal dissent by Foreign Service officers during the Vietnam War, the Department of State designed a process that purported to give those officers a voice to oppose decisions by their superiors called the Dissent Channel. Today, through the Dissent Channel, Foreign Service officers can send dissenting memoranda directly to their superiors. But the Dissent Channel can also be used to neutralize opposition by quarantining dissent within the bureaucracy. The recent revelations by former National Security Agency (NSA) contractor Edward Snowden have demonstrated the impact any government employee with access to sensitive information can have when the employee lacks a constructive outlet for dissent within the bureaucratic structure. This Note addresses the structural allocation of power over foreign policy in the United States’ federalist system and suggests that the current allocation, which heavily favors the President, can be balanced pragmatically only through a robust political check combined with a reinvigorated legislative check, both of which would require a publicized dissent mechanism and protections for dissenters.
Keywords: the Dissent Channel; international treaties; treaty; agreement; American diplomacy; United States foreign policy; checks and balances; Secretary of State; Holmes v. Jennison; Shurtleff v. United States; treaty-making process; State Department; Wilson v. Libby; Joseph Wilson; John Brady Kiesling; Edward Snowden